Analysis of Inflation and Debt on Profit Margins in the Plantation Sub-Sector Listed on the Indonesian Stock Exchange - Mursalini, Wahyu Indah; Yeni, Afni; Afriyaldi, Afriyaldi (Transpublika Publisher, 2024)
The purpose of this study is to investigate the impact of debt and inflation on the profitability of plantation sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Using a sample of 60 data from 12 plantation subsector organizations, the methodology used is quantitative and uses a data approach. correlation. Descriptive statistical tests, multiple linear regression tests, classical assumption tests, and hypothesis tests were used for data analysis, while literature reviews and documentation were used for data collection. The research results show that the inflation variable (X1) has a partial influence on the profit margin (Y) as indicated by the t value of -3.119 which is greater than t table 2.002 and the Sig value of 0.003 which is less than 0.05. Apart from that, the Debt variable (X2) has an influence on Profit Margin (Y) with a Sig value of 0.010 which is smaller than 0.05 and a t-count value of 2.671 which is greater than t-table 2.002. Profit Margin (Y) is influenced simultaneously by inflation (X1) and debt (X2), with a calculated f value of 21.807 greater than f table 3.16 and a Sig value of 0.000 less than 0.05. In the plantation subsector listed on the Indonesia Stock Exchange, the combined influence of debt variables (X2) and inflation (X1) on profit margins (Y) is 43.3%.